Diversity of fruit fly (Diptera: Tephritidae) Species in French Guiana: their main host plants and associated parasitoids during the period 19942003 and prospects for management - Vayssières, Jean-François; Cayol, J.P.; Caplong, P.; Seguret, J.; Midgarden, D.; Sauers-Muller, A.; Zucchi, R.; Uramoto, K.; Malavasi, A. (EDP Sciences, 2013)
This study was carried out in French Guiana, over ten years (1994–2003)by three institutions (SPV, FDGPC and CIRAD); it updates the current state of knowledge ofTephritidae (both Dacini and Toxotrypanini tribes) species present in this country. Materials andmethods. The work was mainly conducted in inhabited areas (from the Brazilian border to theSurinamese border) where cultivated fruit crops are located. Specimens were obtained by adulttrapping and fruit sampling in nearby orchards and at the edge of the rainforest. Trapping wasdone consistently for 10 years, while fruit sampling was a discontinuous activity. We present onlythe results for fruit sampling from three consecutive years (2001–2003) in which a total of 880 kgfrom 45 fruit species in 22 plant families were collected. Results. Twenty-nine plant species fromfourteen plant families were found to be hosts of twenty-one Anastrepha species and oneBactrocera species, Bactrocera carambolae Drew and Hancock. During this period, no specimenof Ceratitis capitata (Wiedemann) was collected in traps or fruit samples. We registered the mainfruit trees which were hosts for B. carambolae and Anastrepha spp. Five hymenopterous parasitoidspecies were identified. Among them, Diachasmimorpha longicaudata (Ashmead) (Hymenoptera,Braconidae) is an exotic species and was introduced into French Guiana in collaboration withBrazilian authorities (EMBRAPA) in 2000 and 2001 within the framework of a classical biologicalcontrol program. Conclusion. Our data provide baseline information about the tephritid species ofeconomic importance present in French Guiana and assist in developing potential future controlprograms of both the B. carambolae and Anastrepha species in the Amazon Basin. These preliminary results are discussed in the light of their implication for rainforest conservation effortsand also evolutionary relationships between fruit flies and their hosts